ANALISIS KASUS PERNIKAHAN DINI DAN KEHAMILAN DI LUAR NIKAH REMAJA DI PONOROGO, JAWA TIMUR: FAKTOR PENYEBAB DAN DAMPAK SOSIAL - Bunga Faisa Nariswari (UNIVERSITAS STEKOM, 2025)
Early marriage and pregnancy outside of marriage among adolescents have become increasingly complex and pressing social problems in Indonesia. This study aims to analyze the factors that drive early marriage and out-of-wedlock pregnancy among adolescents and understand the social impacts on the individuals involved, their families and communities. This study aims to identify and analyze the main causal factors of early marriage and pregnancy outside marriage among adolescents in Indonesia and explore their social impacts. Using a qualitative approach, data was collected through news analysis, journals and relevant literature studies. The results showed that some of the main causal factors of this phenomenon include a lack of sexual education, the influence of social and cultural norms, the role of social media, and family economic factors. In addition, this phenomenon has the potential to hamper education and worsen the economic condition of families, thus risking adding to the social burden of society in the long run. This study recommends increased reproductive health education, social media monitoring, active roles of parents and communities in providing adolescents with a correct understanding of the risks and consequences of early marriage and out-of-wedlock pregnancy, and stricter policies on underage marriage as a prevention effort.